Permasalahan dan Capaian Pelaksanaan Program Pengabdian Merekonstruksi Tata Kota Kerajaan Mengwi - I Nyoman Widya Paramadhyaksa (LPPMK Universitas Ngurah Rai, 2025)
Community Service Activities Bina Desa Program in 2023, which is one of the Merdeka Belajar Kampus Merdeka (MBKM) Programs at Udayana University, takes place in one semester. This activity seeks to inventory and reconstruct the spatial elements and historical buildings of the past of the Mengwi Royal City based on information from sources, photos, and various other documents, then realized in an architectural three-dimensional image and animated video. In the implementation of this program, there were several problems related to the limited data obtained as guidelines for reconstruction, namely: (a) photo data that was difficult to interpret the location where it was taken; (b) information from the sources that was not always in line; (c) the limitations of the sources in remembering and providing information about the past; and (d) the existence of objects and areas that were never entered by the sources. Nevertheless, the activity implementation team finally succeeded in realizing a three-dimensional object description of the elements of the Mengwi Royal City heritage in the past as well as completing this activity.